Immobilization of lipase enzyme from candida antarctica on superparamagnetic maghemite nanoparticles and its behaviour in aqueous and organic catalyses - Kamel Ariffin, Maryam Farhana (2021)
Biocatalysis has emerged as a green technology that is able to replace hazardous and extreme conditions faced in chemical based catalysis. By using magnetized nanomaterials, enhancement on the downstream processing is evident as it eases the immobilized enzyme separation from reaction mixture without having to interfere reaction cavity directly and is able to prepare the enzyme for wide working environment applications. Immobilization of lipase enzyme on superparamagnetic iron oxide nanoparticles is important to maintain the lipase open form as its active sites lie within a conserved catalytic triad which occurs naturally in a closed state. Optimization on synthesis of nanomagnetic materials was conducted using 2.45 GHz microwave. The nanoparticles were synthesized in an aqueous solution of FeCl3.6H2O as precursor and NH3 as nucleating agent. Optimization runs were designed and statistically analyzed using face centered central composite design in Minitab® software. The optimized conditions for microwave assisted synthesis of nanomagnet materials were 100 oC reaction temperature, 20 minutes reaction time at 631 W microwave power producing 0.371 g of magnetic nanoparticles. Based on the characteristic studies done on synthesized nanomagnets by using X-Ray diffraction crystallography, field emission scanning electrom microscopy, attenuated total reflectance – fourier transform infrared spectroscopy and vibrating sample magnetometer, the nanoparticles possessed the same structure as standard maghemite with good magnetic properties. Subsequent maghemite complex cross-linking with glutaraldehyde provide suitable environment for the enzyme to be immobilized. Optimization on the conditions for lipase immobilization was carried out using response surface methodology experimental design to obtain the precise optimized condition for the process. Selected process variables involved were incubation time, reaction temperature and glutaraldehyde content and optimized conditions obtained for lipase immobilization were at 5 hour incubation time, 44 ? incubation temperature and 11 % (v/v) glutaraldehyde content. The optimized immobilized lipase activity in an aqueous based catalysis was 1.49 ±0.05 U. Developed immobilized lipase complex was then subjected for biodiesel production using local sourced refined cooking palm oil as substrate. The work was performed under microwave irradiation to further speed up catalysis reaction. Effects on microwave treatment towards process efficiency were investigated quantitatively using fractional factorial experimental design. It was found that microwave power input, reaction time, immobilized lipase loading and methanol to feed palm oil ratio, affect the biodiesel yield significantly. The highest biodiesel recovery achieved from microwave assisted immobilized lipase catalysed transesterification of palm oil was 70.2 %. The physical properties of produced biodiesel was evaluated and fulfilled the ASTM general requirement for fuels. Based on the findings, the constructed immobilized lipase from Candida antarctica onto maghemite nanoparticles managed to elevate the versatility of immobilized enzymes into wide range of applications by easing the downstream processing with high substrate tolerance and protein stability.